Dental access and expenditures for adults with intellectual and other disabilities. (25th October 2021) - Fosse, Chelsea; Luo, Huabin; Laniado, Nadia; Okunseri, Christopher; Badner, Victor
Abstract: Objectives: Individuals with disabilities experience greater barriers accessing health care services and have poorer oral health outcomes than those without disabilities. The aims of this study were to examine dental access, utilization, expenditures, and sources of payment between adults with intellectual disabilities (ID), other types of disabilities, and without disabilities. Methods: Secondary analyses of data from the 2017 Medical Expenditure Panel Survey (MEPS) allowed examination of dental access (being able to get dental care and receiving necessary dental care without delay), dental utilization (having a dental visit in the past year), total dental expenditures, and associated sources of payment between three groups of adults based on disability status using descriptive, bivariate, and multivariable statistics. Results: Adults with ID have 2.70 (95% CI: 2.03, 3.61) times the odds of being unable to get dental care and 2.88 (95% CI: 2.11, 3.94) times the odds of having to delay necessary dental care compared with adults without disabilities. No significant differences were observed in dental utilization or mean total dental expenditure between the three groups after adjusting for demographic and socioeconomic variables. Among adults who incurred a dental expenditure, adults with ID had a greater share of dental care paid for by Medicaid, and adults without disabilities had a greater share of dental care paid for by private insurance. Conclusions: Despite similar mean total dental expenditures, reduced dental access reported by adults with ID suggests that this population experiences significantly greater challenges obtaining dental care. Adults with ID rely more heavily on Medicaid to finance dental care.